2021
DOI: 10.1111/ases.12930
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation around the gallbladder on plain abdominal computed tomography as a predictor of surgical difficulty in laparoscopic cholecystectomy

Abstract: This study examined whether abdominal plain computed tomography (CT) can predict surgical difficulty in acute cholecystitis. Methods:We retrospectively analyzed 84 consecutive patients who underwent laparoscopic cholecystectomy for acute cholecystitis between January 2015 and December 2018. We distinguished three degrees of surgical difficulty based on the operative time and blood loss: difficult, both ≥120 minutes and ≥ 100 mL, respectively (n = 27); moderate, either ≥120 minutes or ≥ 100 mL, respectively (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Furthermore, risk factors evaluated via a presurgical CT scan vary. Among these factors, CT attenuation, 22 absence of gallbladder wall enhancement, presence of a gallstone in the gallbladder infundibulum, 23 edema in the gallbladder wall, 13 and dirty fat signs 24 have been reported. However, to the best of our knowledge, none of the reports indicated that the maximum diameter of the gallbladder measured via a CT scan was a risk factor for difficult LC in patients with AC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, risk factors evaluated via a presurgical CT scan vary. Among these factors, CT attenuation, 22 absence of gallbladder wall enhancement, presence of a gallstone in the gallbladder infundibulum, 23 edema in the gallbladder wall, 13 and dirty fat signs 24 have been reported. However, to the best of our knowledge, none of the reports indicated that the maximum diameter of the gallbladder measured via a CT scan was a risk factor for difficult LC in patients with AC.…”
Section: Discussionmentioning
confidence: 99%
“…LC has become the gold standard treatment for cholelithiasis [1][2][3]. The application of LC for acute cholecystitis has increased owing to improvements in the procedure and reduced postoperative hospital stay.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy (LC) is the gold standard for cholelithiasis owing to shorter postoperative stay and fewer complications [1][2][3]. Furthermore, LC is the first treatment option for acute cholecystitis [4].…”
Section: Introductionmentioning
confidence: 99%